Introductory Remarks: Disability History - Bower, Alice; Tirosh, Yoav (Scandinavian-Canadian Studies / Études scandinaves au Canada, 2026)
This introduction lays out the theoretical background underlying this special issue of Scandinavian-Canadian Studies, as well as introducing the following articles. This special issue is the direct result of a session entitled “Medieval disability studies: challenges and commonalities”, which was organised by co-editor Yoav Tirosh and Hanna Björg Sigurjónsdóttir at the 16th research conference of the Nordic Network on Disability Research held in Reykjavík, Iceland, in May 2023. We hope that this contribution to the study of disability history will add interesting approaches and case studies to this ever-widening field.